2022
DOI: 10.3389/fmars.2022.912528
|View full text |Cite
|
Sign up to set email alerts
|

Diversity of Free-Living and Particle-Attached Prokaryotes in a River-Influenced Coastal Area of the Northern Adriatic Sea

Abstract: The Northern Adriatic Sea is a key area of the Mediterranean Sea, strongly affected by freshwater inputs, mainly from the Po River, which bring high amounts of nutrients as well as organic and inorganic particles. Free-living and particle-attached prokaryotes were characterized by 16S rRNA gene amplicon sequencing of size-fractionated samples collected during a diatom bloom in this area. The diversity of free-living and particle-attached prokaryotic assemblages was investigated with the aim to understand how t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 120 publications
0
0
0
Order By: Relevance
“…Based on the FAPROTAX analysis, we uncovered that epipelagic-BP connective ASVs held significantly higher carbon cycling functions than BP-specific ASVs. It was consistent with previous observations that particle-associated bacterioplankton carry more abundant active genes than free-living bacteria [26,29,30]. For example, in the Northern Adriatic Sea, one study indicated that most of the functional genes related to substance metabolisms, such as amyA (starch degradation), dmdA (DMSP degradation), ureC (organic nitrogen degradation), and arsC (metal resistance), are more abundant in the particle-associated samples than in the free-living samples [26].…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…Based on the FAPROTAX analysis, we uncovered that epipelagic-BP connective ASVs held significantly higher carbon cycling functions than BP-specific ASVs. It was consistent with previous observations that particle-associated bacterioplankton carry more abundant active genes than free-living bacteria [26,29,30]. For example, in the Northern Adriatic Sea, one study indicated that most of the functional genes related to substance metabolisms, such as amyA (starch degradation), dmdA (DMSP degradation), ureC (organic nitrogen degradation), and arsC (metal resistance), are more abundant in the particle-associated samples than in the free-living samples [26].…”
Section: Discussionsupporting
confidence: 93%
“…It was consistent with previous observations that particle-associated bacterioplankton carry more abundant active genes than free-living bacteria [26,29,30]. For example, in the Northern Adriatic Sea, one study indicated that most of the functional genes related to substance metabolisms, such as amyA (starch degradation), dmdA (DMSP degradation), ureC (organic nitrogen degradation), and arsC (metal resistance), are more abundant in the particle-associated samples than in the free-living samples [26]. Furthermore, the particle-associated communities often demonstrate a broader range of carbon cycling enzyme (e.g., polysaccharide hydrolase) activities than the bulk water community [29,30].…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Our data shows that the long‐term pattern of particle‐associated communities is consistent with these observations, with maximal diversity values in the autumn‐winter transition. On the other hand, as a general rule, richness increases with increasing size fraction in several studies, explained by an increased number of ecological niches (Bižić‐Ionescu et al, 2015 ; Mestre, Borrull et al, 2017 ; Mestre, Ferrera et al, 2017 ; Rieck et al, 2015 ; Yeh & Fuhrman, 2022a ; Yung et al, 2016 ), although higher diversity in free‐living populations have been exceptionally reported in surface (Roth Rosenberg et al, 2021 ; Trano et al, 2022 ) and also in deep marine waters (Salazar et al, 2015 ). Alpha diversity values in the PA communities in our study were higher than those from the FL fraction over all seasons.…”
Section: Discussionmentioning
confidence: 99%